Efficiency Of Sharia Commercial Banks In Indonesia (Two-Stage Analysis) - Risky Dwi Endahsari; Barianto Nurasri Sudarmawan (Eduvest - Journal of Universal Studies, 2024)
This research is motivated by the importance of efficiency in the banking industry, especially in the Islamic banking sector which has a vital role in the Indonesian economy. This study aims to analyze the efficiency of Islamic commercial banks in Indonesia using a two-stage analysis approach. The method used is divided into 2 stages, the first stage is to measure efficiency using the Data Envelopment Analysis (DEA) method to assess the operational performance of banks. The second stage is to analyze the factors that influence efficiency through panel regression. The results of the study indicate that although there are variations in the level of efficiency between banks, factors such as bank size, capitalization, and information technology have a significant influence on efficiency. These findings are expected to provide insight for stakeholders in improving the performance of Islamic banks in Indonesia